Physiological, psychological and behavioural responses of males to cues of sperm competition - Pound, Nicholas (My University, 2000)
Sperm competition theory predicts that males should adjust the number of sperm they inseminate according to the risk of sperm competition. There is experimental evidence that adaptive sperm allocation occurs in many species. However, little attention has been paid to the physiological, psychological and behavioural mechanisms that may allow males to regulate the number of sperm they deliver from one copulation to the next in response to cues of sperm competition risk. The focus of the research reported in this thesis was the elucidation of such mechanisms. A comparative electrophysiological study is reported that demonstrates that the reproductive systems of two related rodent species differ in a way that can be interpreted as a reflection of differential exposure to sperm competition as a selective pressure during their evolutionary histories. Based on this finding it is argued that endogenous opioid systems may be involved in adaptive sperm allocation. In addition, data are presented that indicate that human males are sexually aroused by visual stimuli that would have been reliable cues of increased sperm competition risk in ancestral environments along with an experimental demonstration that human semen parameters can be affected by the nature of the visual stimulation present during specimen production, a finding that may have important clinical implications. Finally, it is shown that there is a relationship between the duration of pre-ejaculatory arousal and the number of sperm in a human male's ejaculate. Consequently, behavioural changes that affect the duration of pre-ejaculatory sexual arousal could potentially be involved in the adaptive regulation of semen parameters in response to changes in the risk of sperm competition.
Keywords: Psychology; Psychology